The ALPINE-ALMA [C ii] survey: Investigation of 10 galaxies at z ∼ 4.5 with [O ii] and [C ii] line emission − ISM properties and [O ii]−SFR relation. Issue 1 (14th January 2022) - Vanderhoof, Brittany N; Faisst, A L; Shen, L; Lemaux, B C; Béthermin, M; Capak, P L; Cassata, P; Le Fèvre, O; Schaerer, D; Silverman, J; Yan, L; Boquien, M; et al.
ABSTRACT: We present 10 main-sequence ALPINE galaxies (log ( M / M ⊙ ) = 9.2−11.1 and SFR=23-190 M_ yr^-1 ) at z ∼ 4.5 with optical [O ii ] measurements from Keck /MOSFIRE spectroscopy and Subaru /MOIRCS narrow-band imaging. This is the largest such multiwavelength sample at these redshifts, combining various measurements in the ultraviolet, optical, and far-infrared including [C ii ]158 μ m line emission and dust continuum from ALMA and H α emission from Spitzer photometry. For the first time, this unique sample allows us to analyse the relation between [O ii ] and total star-formation rate (SFR) and the interstellar medium (ISM) properties via [O ii ]/[C ii ] and [O ii ]/H α luminosity ratios at z ∼ 4.5. The [O ii ]−SFR relation at z ∼ 4.5 cannot be described using standard local descriptions, but is consistent with a metal-dependent relation assuming metallicities around 50 per cent solar. To explain the measured dust-corrected luminosity ratios of (L_[OII]/L_[CII]) 0.98^+0.21_-0.22 and (L_[OII]/L_Hα ) -0.22^+0.13_-0.15 for our sample, ionization parameters log ( U ) < −2 and electron densities (n_e / [cm^-3]) 2.5-3 are required. The former is consistent with galaxies at z ∼ 2−3, however lower than at z > 6. The latter may be slightly higher than expected given the galaxies' specific SFR. The analysis of this pilot sample suggests that typical log ( M /M⊙ ) > 9 galaxies at z ∼ 4.5 to have broadly similar ISM properties as their descendants at z ∼ 2 and suggest a strong evolution of ISM properties since the epoch of reionization at z > 6.